Financial hardship and mortality among older adults using the 1996-2004 Health and Retirement Study - Tucker-Seeley, Reginald D. (2009)
PURPOSE: We investigated the effect of financial hardship on mortality risk in a community-dwelling sample of adults age 50+ in the United States. METHOD: The 1996 Health and Retirement Study cohorts were followed prospectively to 2004 (N=8,377). Gender-stratified grouped Cox models were used to estimate the difference in the RR of mortality between a specific number of financial hardships (one, two, or three or more) and no hardships; and the predictive utility of each individual financial hardship for mortality during the follow up period. RESULTS: Gender-stratified models adjusted for demographics, socioeconomic characteristics, and functional limitations in 1996 showed that women reporting one (HR=1.42, 95% CI, 1.05, 1.92) or three or more (HR=1.60, 95% CI, 1.05, 2.46) and men reporting two (HR=1.80, 95% CI, 1.21, 2.69) financial hardships had a substantially higher probability of mortality compared to those reporting no financial hardships. Individual financial hardships that predicted mortality in fully adjusted models for women included receiving Medicaid (HR=2.23, 95% CI, 1.68, 2.98) and for men receiving Medicaid (HR=2.11, 95% CI, 1.57, 2.84) and receiving food stamps (HR=1.59, 95% CI, 1.09, 2.33). CONCLUSIONS: These findings suggest that over and above the influence of traditional measures of socioeconomic status, financial hardship exerts an influence on the risk of mortality among older adults; and that the number and type of hardships important in predicting mortality may differ for men and women.